Peripheral T Cell Depletion by FTY720 Exacerbates Hypoxic-Ischemic Brain Injury in Neonatal Mice - Herz, Josephine; Köster, Christian; Crasmöller, Marius; Abberger, Hanna; Hansen, Wiebke; Felderhoff-Müser, Ursula; Bendix, Ivo (Frontiers in Immunology, 2018)
Hypoxic-ischemic injury to the developing brain remains a major cause of significant long-term morbidity and mortality. Emerging evidence from neonatal brain injury models suggests a detrimental role for peripheral lymphocytes. The immunomodulatory substance FTY720, a sphingosine-1-phosphate receptor agonist, was shown to reduce adult ischemia-induced neurodegeneration through its lymphopenic mode of action. In the present study, we hypothesized that FTY720 promotes neuroprotection by reducing peripheral lymphocytes and their infiltration into the injured neonatal brain. Term-born equivalent postnatal day 9 C57BL/6 mice were exposed to hypoxia ischemia (HI) followed by a single injection of 1 mg/kg FTY720 or vehicle (0.9% sodium chloride). Brain injury, microglia, and endothelial activation were assessed 7 days post HI using histology and western blot. Peripheral and cerebral leukocyte subsets were analyzed by multichannel flow cytometry. Whether FTY720s’ effects could be attributed to its lymphopenic mode of action was determined in T cell-depleted mice. In contrast to our hypothesis, FTY720 exacerbated HI-induced neuropathology including loss of gray and white matter structures. While microglia and endothelial activation remained unchanged, FTY720 induced a strong and sustained depletion of peripheral T cells resulting in significantly reduced cerebral infiltration of CD4 T cells. CD4 T cell subset analysis revealed that circulating regulatory and effector T cells counts were similarly decreased after FTY720 treatment. However, since neonatal HI per se induces a selective infiltration of Foxp3 positive regulatory T cells compared to Foxp3 negative effector T cells effects of FTY720 on cerebral regulatory T cell infiltration were more pronounced than on effector T cells. Reductions in T lymphocytes, and particularly regulatory T cells coincided with an increased infiltration of innate immune cells, mainly neutrophils and inflammatory macrophages. Importantly anti-CD3-mediated T cell depletion resulted in a similar exacerbation of brain injury, which was not further enhanced by an additional FTY720 treatment. In summary, peripheral T cell depletion by FTY720 resulted in increased infiltration of innate immune cells concomitant to reduced T cell infiltration and exacerbation HI-induced brain injury. This study indicates that neonatal T cells may promote endogenous neuroprotection in the term-born equivalent hypoxic-ischemic brain potentially providing new opportunities for therapeutic intervention.